Rapid annealing of reactively sputtered precursors for Cu2ZnSnS4 solar cells. (10th July 2012) - Scragg, Jonathan J.; Ericson, Tove; Fontané, Xavier; Izquierdo‐Roca, Victor; Pérez‐Rodríguez, Alejandro; Kubart, Tomas; Edoff, Marika; Platzer‐Björkman, Charlotte
ABSTRACT Cu2ZnSnS4 (CZTS) is a promising thin‐film absorber material that presents some interesting challenges in fabrication when compared with Cu(In, Ga)Se2. We introduce a two‐step process for fabrication of CZTS films, involving reactive sputtering of a Cu‐Zn‐Sn‐S precursor followed by rapid annealing. X‐ray diffraction and Raman measurements of the sputtered precursor suggest that it is in a disordered, metastable CZTS phase, similar to the high‐temperature cubic modification reported for CZTS. A few minutes of annealing at 550 °C are sufficient to produce crystalline CZTS films with grain sizes in the micrometer range. The first reported device using this approach has an AM1.5 efficiency of 4.6%, with Jsc and Voc both appearing to be limited by interface recombination. Copyright © 2012 John Wiley & Sons, Ltd.